2000
DOI: 10.1046/j.1524-4733.2000.36028.x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life in Type 2 Diabetes (T2ARDIS-2)

Abstract: This confirms the need for treatment policies to focus on reducing the risk of such complications and hence improve patients' HrQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 5 publications
3
42
1
3
Order By: Relevance
“…23 Glycaemic control is one of the most important factors determining quality of life as poor glycaemic control leads to diabetes related complications which are associated with poor quality of life. 32 Our study found that there was no statistically significant difference in overall quality of life in those having family history of diabetes and those not having it. There are scares data to compare our findings but a study showed that family history of diabetes is more likely to be present in males and is associated with poor disease outcomes like quality of life.…”
Section: Discussioncontrasting
confidence: 51%
“…23 Glycaemic control is one of the most important factors determining quality of life as poor glycaemic control leads to diabetes related complications which are associated with poor quality of life. 32 Our study found that there was no statistically significant difference in overall quality of life in those having family history of diabetes and those not having it. There are scares data to compare our findings but a study showed that family history of diabetes is more likely to be present in males and is associated with poor disease outcomes like quality of life.…”
Section: Discussioncontrasting
confidence: 51%
“…We showed that the patients reported ''some or extreme problems'' in a range of 24.6%-69.3% with highest rate for P/D and A/D dimensions. Review of literature indicated that problems in the P/D and A/D dimensions were most frequently reported [17,21]. Although Sakamaki and his colleague showed that diabetic patients had reported more problem with Mo and P/D dimensions [19].…”
Section: Discussionmentioning
confidence: 99%
“…9 Comparing the health of patient groups with that of comparable members of the general public Self-reported health on the EQ-5D has been compared with age/sex-adjusted population norms for the UK, to gauge the effects on quality of life associated with type 2 diabetes. 15 Determining clinical priorities and managing demand for referral from primary to secondary services. New Zealand's 'points system' for elective surgery utilised specially-designed scoring instruments to determine 'clinical thresholds' and 'financial thresholds' 16 .…”
Section: Application Examples Of Usementioning
confidence: 99%